ผลของโอโซนต่อการสังเคราะห์ด้วยแสงของยางพารา Hevea brasiliensis Muell.Arg - ครรชิต สอสิริกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Photosynthesis of rubber (Hevea brasiliensis) fumigated with ozone at concentration of 200 ppb for 1, 2, 4 and 6h and fumigated with ozone at concentration 100(1h), 300, 600, 900 and 1200 ppb for 2 h compared with ambient air was studied. Photosynthesis (Asat), stomatal conductance (gs), transpiration rate (T), water use efficiency (WUE), leaf greenness and leaf characteristics were measured at 1400 µmol m-2 s-1. Furthermore, light response curve of rubber leaves treated with ozone at concentration of 200 ppb for 1, 2, 4 and 6h compared with control were performed. The data of light response curve were fitted to a non-rectangular hyperbola model to estimate initial slope (α), convexity parameter (θ), maximum photosynthesis (Pmax), dark respiration (Rd), light compensation point (LCP) and light saturation point (LSP).The results showed that Rd, LCP and T of rubber leaves fumigated with ozone at concentration 200 ppb for 2 h significantly decreased. Similarly, Asat, gs and T of rubber leaves fumigated with ozone at concentration of 300-1200 ppb for 2 h significantly decreased. On the other hand, WUE of rubber leaves fumigated with ozone at concentration of 300-900 ppb for 2 h significantly increased. Moreover, rubber leaves treated with ozone at high concentration of 900 and 1200 ppb were injured as characterized by red stippling on adaxial and abaxial leaf surfaces.